Controlling Child Grooming in the Digital World: Public Policy Strategies Based on Media Criminology Studies - Wendi AUDINA; Muhammad ZAKY (International Journal of Environmental, Sustainability, and Social Science, 2025)
Child grooming in the digital realm, particularly through online gaming platforms, has evolved into a complex and systematic form of cybercrime. This study aims to examine the phenomenon of child grooming in the online gaming world from a media criminology perspective, focusing on predatory communication patterns, the dynamics of psychological manipulation of children, and systemic weaknesses in digital child protection regulations in Indonesia. Using a qualitative descriptive approach, data was obtained through literature studies, analysis of reports from institutions such as UNICEF, ECPAT, and the Indonesian Child Protection Commission (KPAI), and articles from national online media. The findings indicate that groomers utilize interactive game features such as voice chat, text chat, and virtual gifts to create emotional closeness, build trust, and ultimately exploit children. Legal loopholes are found in the absence of explicit articles related to the pre-exploitation (grooming) stage in the Child Protection Law and the Electronic Information and Transactions (ITE) Law. Furthermore, content moderation on digital platforms is not yet responsive to the manipulative interactions that precede sexual crimes. Within the media criminology framework, child grooming is understood as a crime amplified by technological infrastructure, social algorithms, and regulatory failures. This study recommends amending laws, strengthening AI-based moderation, curriculum-based digital literacy, and cross-border cooperation as strategic steps to stem the escalation of sexual crimes against children in cyberspace.